Bioinformatics and functional analysis of proteins in serum of early pregnant buffaloes - BALHARA, A K; MOHANTY, A K; GUPTA, MEENAKSHI; JAMWAL, MANU; SUNESH, SUNESH; PHULIA, S K; SINGH, INDERJEET (The Indian Journal of Animal Sciences, 2014)
Bioinformatics using different web based resources was done to classify 2–D gel resolved novel/ up- or down- regulated proteins (n=48) detected in serum of early pregnant buffaloes and find out interactions among them. Proteins were searched for their gene symbols on the ExPASy and the NCBI web portals and then PANTHER software was used to classify them. These proteins were primarily involved in regulatory, catalytic, immune regulation, cell differentiation and transporter functions. Among molecular functions, majority of proteins was involved in either catalytic or binding activities (29.5% each); receptor activity (13.6%), transporter activity (9.1%), enzyme regulator (6.8%) and structural molecule activity (6.8%) besides ion-channel and antioxidant activities. Based on biological functions, maximum (17.6%) proteins were found involved in metabolic function, followed by cellular processes (15.7%). Almost 10.8% proteins were involved in cell communications and 9.8% in transport functions, the rest were involved in immune and developmental processes. To these proteins 23 pathways were assigned, most predominantly Wnt signalling, inflammation - mediated by chemokine and cytokine signalling, and blood coagulation pathways. Other proteins were involved in as many as 20 pathways. A single layer extension to make connections for preparing protein-protein interaction map and network analysis of these bovine proteins, revealed that 9 of these proteins were interacting with each other in 6 different ways - interactions affecting molecular transportation, level of expression, regulation of expression, binding of proteins, interactions resulting in direct regulation and direct regulation inhibition and those leading to modification of the proteins. These findings suggested that the proteins identified with up-regulation, down-regulation or specific appearance at a particular stage during early buffalo pregnancy, primarily act interdependently in the functions involving cellular growth and differentiation.